Preparation process of composite diaphragm and product prepared by preparation process
By forming a composite membrane on the kraft paper of the putty packaging bag, using the combination of primer and topcoat of materials such as polylactic acid emulsion, the problem of moisture and air entering the sealing of the putty packaging bag is solved, extending the storage time of putty and improving the sealing Stability and durability.
Patent Information
- Application Number
- CN202411155433.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-11
AI Technical Summary
During the packaging process, putty packaging bags cause moisture and air to enter due to insufficient sealing properties, causing putty to deteriorate. It is difficult for traditional adhesives and hot melt adhesives to completely fill the pores on the surface of kraft paper, affecting the storage quality of putty.
Using the composite diaphragm preparation process, a discontinuous composite layer is formed on kraft paper by reverse coating primer and gravure surface coating. After wet bonding, a stable primer and surface coating is formed to prevent moisture. and air enter. The primer consists of polylactic acid emulsion, methyl cellulose, glycidyl ester epoxy resin, castor oil polyol, etc. The surface coating contains nano-grade rubber powder, which improves air insulation, waterproofing and chemical resistance.
Effectively prevent moisture and air from entering the putty powder packaging bag, extend the storage time of putty, improve sealing stability and durability, and enhance the structural stability and chemical resistance of the composite membrane.
Smart Images

Figure BDA0005005486980000061 
Figure BDA0005005486980000071 
Figure BDA0005005486980000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite membrane processing, and more specifically, to a composite membrane preparation process and a product obtained therefrom. Background Art
[0002] Putty packaging bags can prevent putty powder from getting damp and contaminated, keeping it dry and pure. Putty powder packaging bags are usually made of multiple layers of materials, mainly including outer layer materials, inner layer materials and middle isolation layers. The outer layer materials and inner layer materials are usually kraft paper, and the middle layer material is usually PE film. This composite film can effectively prevent putty powder from getting damp and contaminated. The inner layer of kraft paper is compounded with the PE film to form a packaging structure with good airtightness, which helps to isolate air and moisture and maintain the quality and stability of putty powder.
[0003] In actual use, putty will be found to change color, harden, clump, etc. The main reason is that the seal of the putty bag is not good when it is packaged. Traditional putty bags are mainly sealed by sewing, using high-strength fiber lines to sew the bottom or side of the bag, which will cause moisture and air to enter the bag and cause the putty to deteriorate.
[0004] In order to prevent moisture and air from entering the package at the sealing point, hot melt glue or adhesive is used for sealing. In the process of bonding, putty powder is generally added first and then bonded. During the adding process, putty powder will adhere to the surface of kraft paper, affecting the bonding stability of hot melt glue and adhesive. Over time, moisture and air will still enter the packaging bag, affecting the quality of putty. Secondly, the surface of kraft paper is uneven. Adhesives and heat sealants are used for bonding. Adhesives and heat sealants cannot completely fill the pores on the surface of kraft paper, which will also cause unstable bonding of hot melt glue and adhesive. As the storage time increases, moisture and air will still enter the packaging bag from the pores, affecting the quality of putty powder. Summary of the invention
[0005] In order to solve the problem of moisture and air entering the seal of the putty packaging bag when it is packaged, the present application provides a composite diaphragm preparation process and the product obtained therefrom.
[0006] In a first aspect, the present application provides a composite membrane preparation process, which adopts the following technical solution: A composite diaphragm preparation process comprises the following preparation steps: S1, reversely coating the kraft paper surface of the composite film with a primer to form a primer layer to obtain a kraft paper composite layer; S2, printing a topcoat on the substrate by gravure printing to form a discontinuous topcoat layer to obtain a composite substrate layer; S3, compounding the kraft paper composite layer with the composite substrate layer by wet lamination, and then bonding the primer layer and the top coat layer by a pressing roller to obtain a composite diaphragm, wherein the wet lamination means that the primer layer and the top coat layer are both in an uncured state and are laminated together; wherein the primer layer is prepared from polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin, castor oil polyol, curing agent and diluent; The top coating is prepared from polylactic acid emulsion, methyl cellulose, glycidyl ester epoxy resin, nano rubber powder, curing agent and diluent.
[0007] By adopting the above technical solution, the surface of the kraft paper is smooth and flat, and the putty powder is not easy to adhere to. The seal of the putty powder packaging bag is stable, and it is not easy for moisture and air to enter, thereby extending the shelf life of the putty powder.
[0008] First, the primer is applied by reverse coating so that the primer can penetrate into the interior of the kraft paper, fill the pores of the kraft paper, prevent air and moisture from entering the putty packaging bag through the kraft paper, and prevent the putty powder from adhering to the surface of the primer when filling the putty powder, which is beneficial to improve the stability of the subsequent putty packaging bag sealing. The glycidyl ester epoxy resin in the primer will combine with the hydroxyl group on the kraft paper when it is cured, so that the primer can stably fit with the kraft paper, and it is also beneficial to combine with the topcoat to improve the stability of the composite diaphragm. Methyl cellulose can improve the fluidity of the primer, making it easier for the primer to penetrate into the interior of the kraft paper and fill the pores of the kraft paper, while making the surface of the primer smoother and less likely to adhere to putty powder; castor oil polyol helps to improve the flexibility and adhesion of the glycidyl ester epoxy resin, thereby further improving the adhesion of the primer to the kraft paper, and at the same time improve the structural stability of the primer, so that it is not easy to be damaged during use.
[0009] Both the topcoat and the primer contain polylactic acid emulsion, methyl cellulose and glycidyl ester epoxy resin, which are conducive to the combination of the topcoat and the primer, so that the topcoat and the primer are firmly connected and not easy to delaminate. The reason is that the topcoat and the primer are attached together in an uncured state, and the components of the two are fused after pressing. A curing reaction occurs in the subsequent curing to form a stable network structure, so that the primer and the topcoat are stably combined and the primer and the topcoat are prevented from separating.
[0010] The topcoat is in direct contact with the putty. The topcoat has good air-tight and waterproof effects, and also has good chemical resistance to avoid being corroded by putty. The reason why most traditional putty packaging bags have a short service life is mainly due to the corrosion of putty powder, which causes aging inside the packaging bag and leakage. In this application, the topcoat is prepared by combining polylactic acid emulsion, methyl cellulose, glycidyl ester epoxy resin, nano-scale rubber powder, curing agent and diluent, which can comprehensively improve the air-tight and waterproof effects, chemical resistance and corrosion resistance of the topcoat, thereby protecting the putty from erosion and damage from the external environment. Among them, the nano-scale rubber powder plays a role of filling, toughening and corrosion protection in the coating. Its tiny particle size enables the rubber powder to be evenly distributed in the coating to form an effective reinforcing phase, further improving the air-tight and waterproof effects, chemical resistance and corrosion resistance of the topcoat. The putty powder packaging bag in this application can be used repeatedly.
[0011] In step S2, gravure printing is used to prevent the substrate layer from forming a discontinuous smooth topcoat layer, which is beneficial to subsequent transfer printing.
[0012] In step S3, the kraft paper composite layer is firstly wet-laminated and then pressed, so that the top coating layer is transferred to the bottom coating layer, and the base layer can be torn off when in use.
[0013] Preferably, the substrate is an OPP film or a PE film.
[0014] The adoption of the above technical solution is conducive to subsequent peeling. OPP film or PE film is a material with a smooth, fleecy surface and low viscosity, and is easy to peel off as a substrate.
[0015] Preferably, the primer is prepared from the following raw materials in weight percentage: Polylactic acid emulsion 20-30% Methylcellulose 4-6% Glycidyl ester epoxy resin 10-15% Castor Oil Polyol 6-10% Curing agent 1-2% The remainder is for dilution.
[0016] By adopting the above technical solution, the amount of raw materials for preparing the primer is optimized, so that the wettability and fluidity of the primer are further increased, which is beneficial for filling the inside of the kraft paper and preventing moisture and air from entering the inside of the packaging bag. At the same time, it can fully combine with the topcoat to form a stable bonding layer, and will not adhere to putty powder after drying.
[0017] Preferably, the topcoat is prepared from the following raw materials in weight percentage: Polylactic acid emulsion 20-30% Methylcellulose 4-6% Glycidyl ester epoxy resin 10-15% Nano rubber powder 5-8% Curing agent 1-2% The remainder is diluent.
[0018] By adopting the above technical scheme, the weight ratio of the raw materials of the topcoat is optimized, the chemical resistance of the topcoat is improved, and the leakage of putty powder is prevented. At the same time, it can be fully combined with the base coating to form a stable bonding layer, thereby improving the durability of the composite diaphragm.
[0019] Preferably, the functionality of the glycidyl ester epoxy resin is 2-4, and the epoxy value is 0.5-0.9.
[0020] By adopting the above technical solution, the bonding stability between the base coating and the kraft paper layer is improved, and the base coating is made denser, reducing the entry of moisture and air into the putty powder packaging bag. In addition, the appropriate balance of functionality and epoxy value can ensure that the coating has good flexibility and crack resistance while maintaining a certain hardness and strength, so as to adapt to the folding and bending requirements of kraft paper and facilitate packaging.
[0021] Preferably, the polylactic acid emulsion is prepared by the following method: 1) dissolving 20-30 parts of polylactic acid in 60-70 parts of solvent by weight to obtain a clear solution; 2) adding 2-3 parts of a water-soluble emulsifier to 30-40 parts of deionized water by weight, stirring until dissolved, and then adding 5-10 parts of a water-soluble chitosan to obtain a mixed solution; 3) The clarified solution and the mixed solution are stirred at a high speed of 1000-1500 r / min to obtain a polylactic acid emulsion.
[0022] By adopting the above technical scheme, the dispersibility of polylactic acid is further improved, so that polylactic acid can be fully and evenly mixed with glycidyl ester type epoxy resin in the primer system and the topcoat system to form a more uniform and stable system, which is beneficial to the coating of the primer and the topcoat.
[0023] The clarified polylactic acid solution obtained in step 1 is slowly added to the mixed solution obtained in step 2. During the addition process, a high-speed stirrer is used to stir at a speed of 1000-1500 rpm. High-speed stirring helps to disperse the polylactic acid solution into tiny droplets, and stably disperse them in the aqueous phase under the action of the emulsifier and the aqueous chitosan, thereby forming a polylactic acid emulsion, so that the polylactic acid emulsion has good fluidity and is conducive to being fully mixed with the glycidyl ester type epoxy resin.
[0024] Preferably, the average particle size of the nano-scale rubber powder is 50-300 nm.
[0025] By adopting the above technical solution, the particle size of the nano rubber powder is optimized, so that the nano rubber powder is evenly distributed in the topcoat system, thereby enhancing the chemical resistance and water-proof and air-proof properties of the topcoat.
[0026] Preferably, the castor oil polyol is obtained by mixing castor oil polyol with a hydroxyl value of 55-60 mgKOH / g, castor oil polyol with a hydroxyl value of 70-100 mgKOH / g and castor oil polyol with a hydroxyl value of 100-150 mgKOH / g in a weight ratio of (8-10):(4-6):3.
[0027] By adopting the above technical solution, the wetting and adhesion properties of the primer layer are improved, and the crosslinking density and toughness of the coating can be improved, which is beneficial to improving the drop resistance of the composite diaphragm. Castor oil polyols with lower hydroxyl values (55-60 mgKOH / g) usually contain longer fatty acid chains, which help to increase the flexibility of the coating. Castor oil polyols with higher hydroxyl values (70-100 mgKOH / g and 100-150 mgKOH / g) contain more hydroxyl groups and can undergo more crosslinking reactions with the curing agent during the curing process, thereby increasing the crosslinking density of the coating and reducing the intrusion of moisture and air.
[0028] Preferably, the coating speed in step S1 is 40-60 m / min and the pressure is 20-25 MPa.
[0029] By adopting the above technical solution, the primer can be stably and evenly coated on the kraft paper, while improving the density and adhesion of the primer. Too little pressure will lead to uneven distribution of the primer and rough coating surface; too much pressure may cause the primer to splash, resulting in waste and affecting the quality of the primer.
[0030] Preferably, in step S3, the temperature of the pressing roller is 110-120° C., the pressure of the pressing roller is 15-20 MPa, and the speed of the pressing roller is 20-25 m / min.
[0031] By adopting the above technical solution, the topcoat layer and the bottomcoat layer are stably connected, and the topcoat layer is transferred. If the temperature of the pressure roller is too high, the bottomcoat layer and the topcoat layer will solidify faster, and the two will solidify before they are completely fused, which will affect the connection stability of the bottomcoat layer and the topcoat layer; if the temperature is too low, the connection between the topcoat layer and the bottomcoat layer will be unstable; appropriate pressure can fully compact the topcoat layer and the bottomcoat layer, improving the density and strength of the product; excessive pressure may cause the material to rupture or deform, and too little pressure may lead to insufficient compaction.
[0032] In a second aspect, the present application provides a composite diaphragm, which adopts the following technical solution: A composite diaphragm comprises a composite membrane, a base coating and a top coating, wherein the base coating is connected to the surface of the kraft paper layer, and the top coating comprises a first top coating and a second top coating, and the first top coating and the second top coating are symmetrically arranged on the surface of the base coating, and the edges of the first top coating and the second top coating do not overlap with the edges of the base coating.
[0033] The composite diaphragm is prepared by the composite diaphragm preparation process described in the first aspect. By adopting the above technical scheme, the prepared composite diaphragm bottom coating does not adhere to putty powder and does not affect subsequent sealing. At the same time, the composite diaphragm has a stable structure, good barrier properties, good chemical resistance and drop resistance, and is easy to package putty powder, greatly extending the packaging time of putty powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the structure of a composite diaphragm in Example 1.
[0035] Figure numerals: 1, composite film; 2, base coating; 3, top coating.
[0036] In summary, this application has the following beneficial effects: 1. Applying a primer on the kraft paper surface of the composite film by reverse coating helps the primer to penetrate into the kraft paper and fill its pores, thereby improving the density and barrier properties of the kraft paper. Among them, the primer is prepared by combining polylactic acid emulsion, methyl cellulose, glycidyl ester epoxy resin, castor oil polyol, curing agent and diluent to ensure that the primer does not adhere to the putty, which is conducive to the subsequent sealing of the packaging bag; the topcoat is prepared by combining polylactic acid emulsion, methyl cellulose, glycidyl ester epoxy resin, nano-grade rubber powder, curing agent and diluent to improve the air-proof and waterproof effect, chemical resistance and corrosion resistance of the topcoat, thereby protecting the putty from erosion and damage from the external environment. At the same time, the primer and the topcoat are combined by wet method to form a firm bonding layer, which effectively prevents air and moisture from entering through the packaging bag, improves the structural stability of the composite diaphragm, makes the barrier have excellent air-proof and waterproof properties, and prolongs the shelf life of the putty powder. DETAILED DESCRIPTION
[0037] Preparation Example The water-soluble chitosan purchased from is carboxylated chitosan with a carboxylation degree of 80%.
[0038] Preparation Example 1 A polylactic acid emulsion is prepared by the following method: 1) dissolving 200 g of polylactic acid in 600 g of solvent (dimethylformamide) to obtain a clear solution; 2) adding 20 g of a water-soluble emulsifier (glycerol monostearate) to 300 g of deionized water, stirring until dissolved, and then adding 50 g of water-soluble chitosan to obtain a mixed solution; 3) The clarified solution and the mixed solution were stirred at a high speed of 1000 r / min to obtain a polylactic acid emulsion.
[0039] The difference between Preparation Example 2-3 and Preparation Example 1 is that the types, amounts and experimental parameters of some raw materials for preparing the polylactic acid emulsion are different. The specific differences are shown in Table 1: Table 1 Experimental data of preparation examples 1-3 Example
[0040] Example 1 A composite diaphragm, such as Figure 1 As shown, it includes a composite film 1, a primer layer 2 and a topcoat layer 3, the primer layer 2 is connected to the surface of the kraft paper layer of the composite film 1, and the topcoat layer 3 includes a first topcoat layer and a second topcoat layer, and the first topcoat layer and the second topcoat layer are symmetrically arranged on the surface of the primer layer 2, and the edge of the first topcoat layer and the edge of the second topcoat layer do not overlap with the edge of the primer layer 2. The area of the first topcoat layer and the second topcoat layer is 10cm*20cm, the area of the primer layer 2 is 14*50cm, and the first topcoat layer and the second topcoat layer are 5cm apart. The distance between the long edge of the first topcoat layer and the second topcoat layer and the long edge of the primer layer 2 is 2cm, and the distance between the long and wide edges of the first topcoat layer and the second topcoat layer and the wide edge of the primer layer 2 is 2.5cm.
[0041] The composite diaphragm is prepared by the following method: S1. Reversely apply a primer on the kraft paper surface of the composite film to form a primer layer, with a coating speed of 40 m / min, a coating pressure of 20 MPa, and a coating wet weight of 6 g / m2 to obtain a kraft paper composite layer; S2, printing a topcoat on the substrate by gravure printing to form a discontinuous topcoat layer to obtain a composite substrate layer; S3, compounding the kraft paper composite layer with the composite substrate layer by wet lamination, and then passing through a pressure roller, the pressure roller speed is 20m / min, the pressure roller pressure is 15MPa, the coating wet weight is 10g / m2, so that the primer layer and the top coat are bonded to obtain a composite diaphragm, the wet lamination means that the primer layer and the top coat are both in an uncured state, and are then laminated together; The primer is prepared from 200 g of polylactic acid emulsion (from Preparation Example 1), 40 g of methyl cellulose, 100 g of glycidyl ester epoxy resin, 60 g of castor oil polyol, 10 g of curing agent (triglycidyl isocyanurate) and 300 g of diluent (alkylene glycidyl ether); The top coating is prepared from 200 g of polylactic acid emulsion (from Preparation Example 1), 40 g of methyl cellulose, 100 g of glycidyl ester epoxy resin, 50 g of nano rubber powder, 10 g of curing agent (triglycidyl isocyanurate) and 300 g of diluent (alkylene glycidyl ether).
[0042] The glycidyl ester epoxy resin is a diglycidyl adipate epoxy resin, has a functionality of 2, and an epoxy value of 0.5.
[0043] The hydroxyl value of castor oil polyol is 55 mgKOH / g.
[0044] The average particle size of the nano rubber powder is 50nm. It is nitrile rubber, the brand is Kaiming Plastic, and the model is SH-830.
[0045] The base material is PE film.
[0046] The difference between Example 2-3 and Example 1 is that the types, amounts and experimental parameters of some raw materials for preparing the composite diaphragm are different. The specific differences are shown in Table 2: Table 2 Experimental data of Examples 1-3 Example 4 A composite diaphragm. The difference between this embodiment and embodiment 1 is that the castor oil polyol is obtained by mixing castor oil polyol with a hydroxyl value of 55 mgKOH / g, castor oil polyol with a hydroxyl value of 70 mgKOH / g and castor oil polyol with a hydroxyl value of 100 mgKOH / g in a weight ratio of 8:4:3.
[0047] Example 5 A composite diaphragm. The difference between this embodiment and embodiment 1 is that the castor oil polyol is obtained by mixing castor oil polyol with a hydroxyl value of 60 mgKOH / g, castor oil polyol with a hydroxyl value of 100 mgKOH / g and castor oil polyol with a hydroxyl value of 150 mgKOH / g in a weight ratio of 10:6:3.
[0048] Example 6 A composite diaphragm. The difference between this embodiment and embodiment 1 is that the castor oil polyol is obtained by mixing castor oil polyol having a hydroxyl value of 55 mgKOH / g and castor oil polyol having a hydroxyl value of 70 mgKOH / g in a weight ratio of 8:7.
[0049] Example 7 A composite diaphragm. The difference between this embodiment and embodiment 1 is that the castor oil polyol is obtained by mixing castor oil polyol with a hydroxyl value of 55 mgKOH / g and castor oil polyol with a hydroxyl value of 100 mgKOH / g in a weight ratio of 8:7.
[0050] Example 8 A composite diaphragm. The difference between this embodiment and embodiment 1 is that the castor oil polyol is obtained by mixing castor oil polyol with a hydroxyl value of 70 mgKOH / g and castor oil polyol with a hydroxyl value of 100 mgKOH / g in a weight ratio of 4:11.
[0051] Example 9 A composite diaphragm, the difference between this embodiment and embodiment 1 is that: the coating speed in step S1 is 40m / min, and the pressure is 15MPa.
[0052] Example 10 A composite diaphragm, the difference between this embodiment and embodiment 1 is that: in step S3, the temperature of the pressing roller is 130°C, the pressure of the pressing roller is 15 MPa, and the speed of the pressing roller is 20 m / min.
[0053] Embodiment 11 A composite diaphragm, the difference between this embodiment and embodiment 1 is that: in step S3, the temperature of the pressing roller is 110° C., the pressure of the pressing roller is 10 MPa, and the speed of the pressing roller is 20 m / min.
[0054] Comparative Example Comparative Example 1 A composite diaphragm, this comparative example is different from Example 1 in that it has no primer layer.
[0055] Comparative Example 2 A composite diaphragm, the difference between this comparative example and Example 1 is that a straight coating method is adopted in step S1.
[0056] Comparative Example 3 A composite diaphragm. This comparative example is different from Example 1 in that screen printing is used in step S2.
[0057] Comparative Example 4 A composite diaphragm. The difference between this comparative example and Example 1 is that in step S3, both the primer layer and the top layer are completely cured.
[0058] Comparative Example 5 A composite diaphragm. The difference between this comparative example and Example 1 is that acrylic polymer emulsion is used in the primer instead of polylactic acid emulsion.
[0059] Dow acrylic polymer emulsion PRIMAL NW-5118 acrylic emulsion.
[0060] Comparative Example 6 A composite diaphragm. The difference between this comparative example and Example 1 is that aliphatic epoxy resin is used in the primer instead of glycidyl ester epoxy resin.
[0061] The aliphatic epoxy resin is Dow's aliphatic flexible epoxy resin DER732.
[0062] Comparative Example 7 A composite diaphragm. This comparative example is different from Example 1 in that carboxymethyl cellulose is used in the primer instead of methyl cellulose.
[0063] Comparative Example 8 A composite diaphragm. This comparative example is different from Example 1 in that polyether polyol is used in the primer instead of castor oil polyol.
[0064] The molecular weight of the polyether polyol is 5,000.
[0065] Comparative Example 9 A composite diaphragm. The difference between this comparative example and Example 1 is that silicon dioxide is used in the top coating instead of nano-grade rubber powder.
[0066] Comparative Example 10 A composite diaphragm. The difference between this comparative example and Example 1 is that the particle size of the rubber powder is 1 micron.
[0067] Comparative Example 11 A composite diaphragm. The difference between this comparative example and Example 1 is that acrylic polymer emulsion is used in the top coating instead of polylactic acid emulsion.
[0068] Dow acrylic polymer emulsion PRIMAL NW-5118 acrylic emulsion.
[0069] Comparative Example 12 A composite diaphragm. The difference between this comparative example and Example 1 is that aliphatic epoxy resin is used in the primer instead of glycidyl ester epoxy resin.
[0070] The aliphatic epoxy resin is Dow's aliphatic flexible epoxy resin DER732.
[0071] Comparative Example 13 A composite diaphragm. This comparative example is different from Example 1 in that BASF joncryl HPB is used instead of the primer.
[0072] Detection method / test method Putty powder adhesion test: Prepare composite diaphragms using Examples 1-11 and Comparative Examples 1-13, tear off the substrate layer, immerse them in putty powder respectively, keep for 1 minute, take them out, shake them, and observe whether the surface of the base coating layer is adhered to putty powder. If it is adhered to powder, no further test experiments will be performed.
[0073] Sealing test: If there is no residual putty powder in the putty powder adhesion test, continue to do the sealing test. Apply adhesive to the primer surface, leave one side uncoated with adhesive, fold it in half along the center line of the primer, knead it to form a packaging bag, leave one side uncoated with adhesive to form a seal, then add 15g putty powder, apply the adhesive to seal, seal, weigh, then put it in 80℃ water, soak for 20 days, take it out, wipe off the water, weigh it, and calculate the increased weight.
[0074] Adhesion stability test of kraft paper layer, base coating and top coating: Prepare a composite diaphragm using Examples 1-11 and Comparative Examples 1-13, tear off the substrate layer, soak it in 15% by mass hydrogen peroxide for 5 days, take it out, wipe dry, and fix it. Then use a hair dryer to blow air along the side at a wind speed of 50m / s for 1 hour to observe whether the layers are separated.
[0075] Chemical resistance test: Tear off the substrate layer, apply adhesive on the primer surface, leave one side uncoated with adhesive, fold it in half along the center line of the primer layer, knead it to form a packaging bag, leave one side uncoated with adhesive to form a seal, then add half the volume mass concentration of 20% sodium hydroxide solution, apply adhesive on the primer surface, seal the seal, place it in an environment with a humidity of 90% and a temperature of 80°C, record the leakage time of the packaging bag, and if there is no leakage after 1000h, stop the test and record it as no leakage.
[0076] Drop resistance test: Leave one side uncoated with adhesive, fold along the center line of the base coating, knead to form a packaging bag, leave one side uncoated with adhesive to form a seal, then add half the volume of putty powder, and then apply the adhesive to seal the bag to obtain a sample, select a smooth cement floor, let the sample fall freely from a height of 3m, and observe whether the packaging bag is damaged. The experimental data is shown in Table 3: Table 3 Experimental data of Examples 1-11 and Comparative Examples 1-13 By comparing Example 1 with Comparative Examples 1-4, in Comparative Example 1, putty was adhered in the putty powder adhesion test; in the sealing test, the weight increase of Comparative Examples 2-4 was much greater than that of Example 1, especially the largest increase of Comparative Example 2; in the adhesion stability test of the kraft paper layer, the base coat and the top coat, the kraft paper and the base coat were separated in Comparative Examples 2-3, and the base coat and the top coat were separated in Comparative Example 4; in the chemical resistance test, the leakage time of Comparative Examples 2-4 was significantly shorter. From the results of Comparative Examples 1-4 and Example 1, the composite diaphragm prepared by the preparation process in the present application is not stained with putty powder and is easy to seal, and also has good structural stability, barrier properties, chemical resistance and drop resistance.
[0077] By comparing Example 1 with Comparative Examples 5-8, in Comparative Example 5, putty was adhered in the putty powder adhesion test; in the sealing test, the weight increase of Comparative Examples 6-8 was much greater than that of Example 1; in the adhesion stability test of the kraft paper layer, the base coating and the top coating, separation of the kraft paper, the base coating and the top coating occurred in Comparative Examples 6 and 8; in the chemical resistance test, the leakage time of Comparative Examples 6-8 was significantly shorter; in the drop resistance test, damage occurred in Comparative Example 6. From the results of Comparative Examples 5-8 and Example 1, it is shown that by preparing the primer with polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin and castor oil polyol, the adhesion of putty to the primer surface can be effectively prevented, and the structural stability, barrier performance, chemical resistance and drop resistance of the composite diaphragm can be effectively improved.
[0078] By comparing Example 1 with Comparative Examples 9-12, in the adhesion stability test of the kraft paper layer, the base coating layer and the top coating layer, the kraft paper, the base coating layer and the top coating layer separated in Comparative Examples 11-12; in the chemical resistance test, the leakage time of Comparative Examples 9-12 was significantly shorter; in the drop resistance test, damage occurred in Comparative Examples 9-10 and 12. From the results of Comparative Examples 9-12 and Example 1, it can be seen that the structural stability, barrier performance, chemical resistance and drop resistance of the composite diaphragm can be effectively improved by preparing the top coating with polylactic acid emulsion, methyl cellulose, glycidyl ester type epoxy resin and nano rubber powder.
[0079] By comparing Example 1 with Comparative Example 13, in Comparative Example 13, putty adhered in the putty powder adhesion test, indicating that the base coating in the present application does not stick to putty powder.
[0080] Comparing Example 1 with Examples 4-8, in the sealing test, the weight of Examples 4-5 did not increase substantially, and the weight increase of Examples 5-8 was greater than that of Example 1; in the chemical resistance test, no leakage occurred in Examples 4-5, and the leakage time of Examples 6-8 was shorter than that of Example 1, indicating that mixing castor oil polyester polyols with different hydroxyl values can effectively improve the barrier properties and chemical resistance of the composite diaphragm.
[0081] Comparing Example 1 with Examples 9-11, in the sealing test, the weight increase of Examples 9-11 is greater than that of Example 1; in the adhesion stability test of the kraft paper layer, the primer layer and the top coat layer, the primer layer and the top coat layer are separated in Example 9; in the chemical resistance test, the leakage time of Examples 9-11 is shorter than that of Example 1. From the experimental results of Examples 1 and Examples 9-11, it can be seen that by optimizing the speed of the primer and the temperature of the pressure roller, the barrier properties, chemical resistance and structural stability of the composite diaphragm can be effectively improved.
[0082] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A composite diaphragm preparation process, characterized in that: The method comprises the following preparation steps: S1, reversely coating the kraft paper surface of the composite film with a primer to form a primer layer to obtain a kraft paper composite layer; S2, printing a topcoat on the substrate by gravure printing to form a discontinuous topcoat layer to obtain a composite substrate layer; S3, compounding the kraft paper composite layer with the composite substrate layer by wet lamination, and then bonding the primer layer and the top coat layer by a pressing roller to obtain a composite diaphragm, wherein the wet lamination means that the primer layer and the top coat layer are both in an uncured state and are then bonded together; The primer is prepared from polylactic acid emulsion, methyl cellulose, glycidyl ester epoxy resin, castor oil polyol, curing agent and diluent; The top coating is prepared from polylactic acid emulsion, methyl cellulose, glycidyl ester epoxy resin, nano rubber powder, curing agent and diluent.
2. A composite diaphragm preparation process according to claim 1, characterized in that: The primer is prepared from the following raw materials in weight percentage: Polylactic acid emulsion 20-30% Methylcellulose 4-6% Glycidyl ester epoxy resin 10-15% Castor Oil Polyol 6-10% Curing agent 1-2% The remainder is diluent.
3. A composite diaphragm preparation process according to claim 2, characterized in that: The topcoat is prepared from the following raw materials in weight percentage: Polylactic acid emulsion 20-30% Methylcellulose 4-6% Glycidyl ester epoxy resin 10-15% Nano rubber powder 5-8% Curing agent 1-2% The remainder is diluent.
4. A composite diaphragm preparation process according to claim 1, characterized in that: The functionality of the glycidyl ester epoxy resin is 2-4, and the epoxy value is 0.5-0.9 mol / 100g.
5. A composite diaphragm preparation process according to claim 1, characterized in that: The polylactic acid emulsion is prepared by the following method: 1) Dissolve 20-30 parts of polylactic acid in 60-70 parts of solvent by weight to obtain a clear solution; 2) Add 2-3 parts of water-soluble emulsifier to 30-40 parts of deionized water by weight, stir until dissolved, and then add 5-10 parts of water-soluble chitosan to obtain a mixed solution; 3) The clarified solution and the mixed solution are stirred at a high speed of 1000-1500 r / min to obtain a polylactic acid emulsion.
6. A composite diaphragm preparation process according to claim 4, characterized in that: The average particle size of the nano rubber powder is 50-300nm.
7. A composite diaphragm preparation process according to claim 1, characterized in that: The castor oil polyol is obtained by mixing castor oil polyol with a hydroxyl value of 55-60 mgKOH / g, castor oil polyol with a hydroxyl value of 70-100 mgKOH / g and castor oil polyol with a hydroxyl value of 100-150 mgKOH / g in a weight ratio of (8-10): (4-6):
3.
8. A composite diaphragm preparation process according to claim 1, characterized in that: The coating speed in step S1 is 40-60 m / min and the pressure is 20-25 MPa.
9. A composite diaphragm preparation process according to claim 1, characterized in that: In step S3, the temperature of the pressing roller is 110-120°C, the pressure of the pressing roller is 15-20 MPa, and the speed of the pressing roller is 20-25 m / min.
10. A composite diaphragm, characterized in that: The composite diaphragm comprises a composite film, a base coating and a top coating, wherein the base coating is connected to the surface of the kraft paper layer, and the top coating comprises a first top coating and a second top coating, wherein the first top coating and the second top coating are symmetrically arranged on the surface of the base coating, and the edges of the first top coating and the second top coating do not overlap with the edges of the base coating; The composite diaphragm is prepared by the composite diaphragm preparation process described in any one of claims 1-9.
Citation Information
Patent Citations
Novel treated mineral pigments for aqueous based barrier coatings
CN102575433A
High-barrier kraft paper compound film and compounding equipment thereof
CN112626913A
Composite film bag with paper touch feeling
CN216944282U
